Secondary metabolites of the granular form of Pseudomonas fluorescens P60 and its applications to control tomato bacterial wilt - LOEKAS SOESANTO; DHIMAS AULI SAPUTRA; MURTI WISNU RAGIL SASTYAWAN; ENDANG MUGIASTUTI; AGUS SUPRAPTO; RUTH FETI RAHAYUNIATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Soesanto L, Saputra DA, Sastyawan MWR, Mugiastuti E, Suprapto A, Rahayuniati RF. 2023. Secondary metabolites of the granular form of Pseudomonas fluorescens P60 and its applications to control tomato bacterial wilt. Biodiversitas 24: 2475-2482. Bacterial wilt is one of the important diseases of tomatoes caused by Ralstonia solanacearum (Smith 1896) Yabuuchi et al. 1996. Its control can be achieved by applying secondary metabolites of Pseudomonas fluorescens Migula 1895 P60 in granular form. The study aimed to determine the shelf life of the secondary metabolites P. fluorescens P60' in granular form and its application to manage bacterial wilt and the performance of tomatoes. The study was conducted for five months at the Plant Protection Laboratory and Experimental Farm, Faculty of Agriculture, Universitas Jenderal Soedirman. A randomized block design was used with four replicates and six treatments, consisting of R. solanacearum (control), R. solanacearum + 1, 5, 10, or 15 g, and bactericide (a.i. agrimycin sulphate 20%). Variables observed were inhibition zone, incubation period, disease intensity, the area under disease progress curve (AUDPC), crop height, crop fresh and dry weight, root fresh and dry weight, and phenolic compounds qualitatively. Results of the research showed that the granular formula until the 4th week still had an inhibition zone between 21.67-23.34%. However, the granules stored for as much as 15 g for four weeks effectively reduced disease intensity by 75.00%, decreased AUDPC value by 74.72%, and increased plant height, root dry weight, and fresh crop weight as well 44, 62.5, and 65.65 %, respectively. In addition, the granular formula increased the content of tomato phenolic compounds qualitatively.